THE USE OF DRILLING TECHNIQUES INTEGRATED WITH TECHNOLOGY TO IMPROVE STUDENTS’ VOCABULARY MASTERY AT SD NEGERI 3 DALUNG - Dewi Sariani, Ni Kadek Ayu; Dewi, Kadek Sintya; Mahendrayana, Gede (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2025)
This study aims to improve the mastery of English vocabulary of fourth grade students of SD Negeri 3 Dalung through drilling techniques integrated with technology in the form of vocabulary videos. The drilling technique was chosen because it is effective in improving students' memory through repetition of material, while the technology in the form of videos provides an interactive and interesting learning experience. The research method used is Classroom Action Research (CAR) with two cycles, where each cycle consists of the stages of planning, action, observation, and reflection. Data were collected through vocabulary tests, observations, and interviews. The results showed that the use of drilling techniques integrated with vocabulary videos significantly improved students' vocabulary acquisition. At the end of the second cycle, the number of students who reached the Minimum Completion Criteria (KKM) increased significantly compared to the first cycle. In addition, students showed improvement in confidence and active participation during the learning process. The use of technology through video media also enriched students' learning experience and motivated them to better understand English vocabulary. The findings provide practical implications for teachers to adopt technology-based learning methods to support students' vocabulary acquisition effectively.